Dairy goat health management and milk production on organic and conventional system in Brazil - Da Silva, Jenevaldo Barbosa [UNESP]; Fagundes, Gisele Maria; Soares, João Paulo Guimarães; Fonseca, Adivaldo Henrique (Universidade Estadual de Londrina, 2013)
The aimed of this article is to measure risk factors on health and milk production on organic and conventional dairy goats in Brazil. Two experimental groups (organic and conventional) were evaluated simultaneously. The study design was completely randomized. The organic herd consisted of 25 goats and 15 kids. In the conventional production system, a dairy herd comprising 40 goats and 20 kids participated in the study. Data on milk production and health management were available from January 2007 to December 2009. The abortion rate in the conventional system was 5% (2/40) whereas in organic system no abortion was diagnosed (0/25). The mortality rate at weaning in the conventional system was 5% (2/40) and in the organic system was 8% (2/25). Milk production was lower (2.20 kg/day) in organic than conventional system (2.66 kg/day). Goats and kids in organic farm had a higher FEC (386±104 and 900±204, respectively) (p<0.05) than those in conventional farm (245±132 and 634±212, respectively). In addition, Saanen kids had higher FEC (p<0.001) than goats. Treatment with antiparasitic drugs was higher in conventional system (50%) than organic system (1.3%).
Keywords: Conventional system; Goat; Milk production; Organic system; Parasites